2014
DOI: 10.2965/jwet.2014.65
|View full text |Cite
|
Sign up to set email alerts
|

Operational Factors in Membrane Bioreactors Using a Simple Ceramic Filter

Abstract: To explore the cost reduction of water reclamation and reuse facilities in developing countries, a simple ceramic filter made of local materials, such as clay and rice bran, was used in a membrane bioreactor (MBR) process. The feasibility of applying suction filtration to an MBR with a simple ceramic filter was examined by a laboratory-scale experiment; successful results using gravity filtration were reported in a previous paper. The BOD removal performance was satisfactory and demonstrated the feasibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have reported substantial removal (over 93%) of iron, manganese, and phosphorus (Hasan et al 2015) from groundwater because of the effective floc separation performance of the ceramsite filter system. This material was also used in the MBR process to treat wastewater with satisfactory removal performance of different pollutants for instance 97-100% of BOD, 96-100% of COD, 98-100% of TOC, more than 98% of nitrogen and more than 96% of phosphorus (Hasan & Nakajima 2014). These results signify that the light ceramic filter might also offer a simple approach to improve the effluent quality of graywater which has not been reported to date.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies have reported substantial removal (over 93%) of iron, manganese, and phosphorus (Hasan et al 2015) from groundwater because of the effective floc separation performance of the ceramsite filter system. This material was also used in the MBR process to treat wastewater with satisfactory removal performance of different pollutants for instance 97-100% of BOD, 96-100% of COD, 98-100% of TOC, more than 98% of nitrogen and more than 96% of phosphorus (Hasan & Nakajima 2014). These results signify that the light ceramic filter might also offer a simple approach to improve the effluent quality of graywater which has not been reported to date.…”
Section: Introductionmentioning
confidence: 90%
“…As a new filter material, micro-porous ceramic has lower density and higher specific surface area as compared to conventional micro-filtration membrane media such as cellulose acetate, polyvinylidene fluoride (PVDF), and polyethersulfone (PES) [17]. The ceramic filter has been reported to satisfactorily remove different pollutants in drinking water treatment, i.e., 40-58% for TOC and more than 70% for nitrogen [18,19]. These signify that employing ceramic membrane is very likely to achieve the desired results in rainwater treatment which has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%